Link Budget Prediction at 28 GHz Frequency Based on Rain Attenuation Model in Palembang City - Tarnita Rizky Prihandhita; Sopian Soim; Mohammad Fadhli (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
5G communication technology brings a major leap in the development of wireless networks, especially through the utilization of millimeter wave frequencies. However, mmWave signals are very susceptible to rain attenuation, which can significantly reduce the quality of 5G services. This study aims to estimate how much signal loss and reception power there will be for 5G at a frequency of 28 GHz in Palembang City and to examine how rain affects the mmWave signals. MATLAB simulations use Palembang rainfall data for the March 2025 period and use the ITU-R P.618-5 rain attenuation model, Simple Attenuation Model, and ITU-R Tropical. Using the Urban Macro propagation scenario in line-of-sight and non-line-of-sight conditions. The results show that distance and rainfall affect signal attenuation, with NLOS conditions producing worse attenuation than LOS. At high rainfall of 84.5 mm/hour in NLOS conditions, ITU-R P.618-5 predicts the highest total path loss of about 317 dB, ITU-R Tropical about 247 dB, and SAM about 227 dB. With the received power of ITU-R P.618-5 model of -260 dBm, ITU-R Tropical of -190 dBm, and SAM of -170 dBm.